PENGARUH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP PEMBENTUKAN KARAKTER RELIGIUS PADA SISWA KELAS VIII DI SMP MUAMMADIYAH SIMPANG EMPAT - Farida Afifah Nur Raidah (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2013)
This study aims to determine: 1) Learning Islamic religious education in the 8th grade of SMP Muhammadiyah Simpang Empat, 2) The formation of religious character in 8th grade students at SMP Muhammadiyah Simpang Empat, and 3) The influence of Islamic religious education learning on the formation of religious character in 8th grade students at SMP Muhammadiyah Simpang Empat for the 2019/ 2020 school year. This research uses a quantitative approach and descriptive research type. The population in this study were students of grade 8, amounting to 139 people with the sample used as many as 46 people. The data collection tools using questionnaires, observation, and documentation. The previous questionnaire was tried out and tested for validity and reliability testing. The data analysis technique used the product moment correlation and the coefficient of determination. The research results can be concluded as follows: 1) Learning Islamic religious education in the 8th grade of SMP Muhammadiyah Simpang Empat is included in the “low” category with an average score of 35.20, 2) The formation of religious character in 8th grade students at SMP Muhammadiyah Simpang Empat is included in the “medium” category with an average score of 42.24, and 3) There is significant influence between learning Islamic religious education on the formation of religious character in 8th grade students at SMP Muhammadiyah Simpang Empat for the 2019/ 2020 school year. This is evidenced by the calculation of rcount of 0.850. At a significance level of 5% or α= 0.05, the rtable value is 0.297. Because the value of rcount ≥ rtable is 0.850 ≥ 0.297, so Ho is rejected and Ha is accepted which says there is a significant influence between learning Islamic religious education on the formation of religious character in 8th grade students at SMP Muhammadiyah Simpang Empat.